Cas12a RNP-mediated co-transformation enables transgene-free multiplex genome editing, long deletions, and inversions in citrus chromosome - Su, Hang; Wang, Yuanchun; Xu, Jin; Omar, Ahmad A.; Grosser, Jude W.; Wang, Nian (Frontiers in Plant Science, 2024)
Citrus canker, caused by Xanthomonas citri subsp. citri (Xcc), is a devastating disease worldwide. Previously, we successfully generated canker-resistant Citrus sinensis cv. Hamlin lines in the T0 generation, achieving a mutation efficiency of 97.4%. This was achieved through the transformation of embryogenic protoplasts using the Cas12a/1 crRNA ribonucleoprotein (RNP) system to edit the canker susceptibility gene, CsLOB1, which led to small indels. Here, we transformed embryogenic protoplasts of Hamlin with Cas12a/3 crRNAs RNP, resulting in 100% efficiency in editing the CsLOB1 gene in the T0 generation. Among the 10 transgene-free genome-edited lines, long deletions were obtained in five lines. Additionally, inversions were observed in three of the five edited lines with long deletions, but not in any edited lines with short indel mutations, suggesting long deletions maybe required for inversions. Biallelic mutations were observed for each of the three target sites in 4 of the 10 edited lines when 3 crRNAs were used, demonstrating that transformation of embryogenic citrus protoplasts with Cas12a/3 crRNAs RNP can be very efficient for multiplex editing. Our analysis revealed the absence of off-target mutations in the edited lines. These cslob1 mutant lines were canker-resistant and no canker symptoms were observed after inoculation with Xcc and Xcc growth was significantly reduced in the cslob1 mutant lines compared to the wild type plants. Taken together, Cas12a/3 crRNAs RNP transformation of embryogenic protoplasts of citrus provides a promising solution for transgene-free multiplex genome editing with high efficiency and for deletion of long fragments.